Trends in wireless communication and information security proceedings of EWCIS 2020 ; 8-9 October, 2020, Ranchi, India - Chakraborty, Mithun; Jha, Raman Kr; Balas, Valentina Emilia; Sur, Samarendra Nath; Kandar, Debdatta (Lecture Notes in Electrical Engineering, 2021)
This book presents best selected papers presented at the International Conference on Emerging Wireless Communication Technologies and Information Security (EWCIS 2020), held from 8th & 9th October 2020 at Amity University Jharkhand, Ranchi, India. The book includes papers in the research area of wireless communications and intelligent systems, signal and image processing in engineering applications, data communication and information security, IoT and cloud computing. The contribution ranges from scientists, engineers and technologists from academia as well as from industry.